Optimisation of properties of silicon carbide ceramics with the use of different additives - Lobach, K.; Kupriiyanova, Y.; Kolodiy, I.; Sayenko, S.; Shkuropatenko, V.; Voyevodin, V.; Zykova, A.; Bykov, A.; Chunyayev, O.; Tovazhnyanskyy, L. (Functional Materials, 2018)
The influence of different additions on the densification behavior of SiC based ceramics has been investigated. The SiC matrices reinforced by additives of amorphous B, Cr, Si were fabricated using High Speed Hot Pressing Method. Additives content was in the range from 0.5 to 3 wt. %. Microstructural characteristics of silicon carbide ceramics were analyzed by X-ray diffraction, scanning electron microscopy and elemental distribution analyses. A fine-grained and dense ceramics with advanced mechanical properties were produced at optimal processing conditions. SiC ceramics with Cr and Si additives possess the best structural and mechanical characteristics: micro hardness 28.0-30 GPa and fracture toughness K1C = 6.2-4.7 ċm¹/², respectively. The sintering process by High-Speed Hot Pressing Method leads to the fine-grained structure formation and increase of the fracture toughness of ceramics. The structural and mechanical properties of SiC ceramics can be improved by effective additives content controlling.